Understanding risk factors in road traffic accidents among young motorcyclists aged 18-24: a scoping review: 10.55131/jphd/2025/230123 - Setyowati, Dina; Shaluhiyah, Zahroh; Widjanarko, Bagoes; Setyaningsih, Yuliani (Journal of Public Health and Development, 2024)
Road traffic accidents (RTAs) are global public health issues affecting young motorcyclists aged 18-24 years due to their risky behaviors, such as emotional, rushed, and careless driving. Therefore, this review aimed to identify and analyze risk factors contributing to RTAs among young motorcyclists. The procedures began with a comprehensive search on Scopus, ScienceDirect, and PubMed databases for studies published between 2019 and 2022 using Arksey and O'Malley's framework as well as the PRISMA-ScR checklist. Based on the search results, a total of 13 peer-reviewed studies met stringent inclusion criteria, focusing on individuals aged 18-24 driving 2-wheeled motorcycles. Critical appraisal results using Joanna Briggs Institute (JBI) tools showed several key factors influencing RTA rates, including age and gender differences, sensation-seeking behavior, as well as social and environmental impacts, particularly peer passenger influence. This indicates the urgent need for targeted interventions, such as age-specific educational programs and stricter regulations, and calls for longitudinal studies to assess the long-term effectiveness of the interventions. Integrating these results into policy frameworks is crucial for reducing accidents among young motorcyclists, advocating for a comprehensive approach that combines education, regulation, and ongoing evaluation to enhance road safety.